Penggunaan Smartphone Berpengaruh Terhadap Gejala Computer Vision Syndrome: Smartphone's Usage Affects Computer Vision Syndrome Symptoms - Sofia Apriyanti; Endang Sawitri; Nur Khoma Fatmawati (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Smartphones which are very useful in human life can cause health related problem due to excessive and improper use. The improper duration and distance when using smartphone will cause symptoms of Computer Vision Syndrome (CVS). This study used a cross – sectional approach with an observational analytic research design to determine the relationship between duration and distance of smartphone's usage with the symptoms of CVS in students of the Faculty of Medicine, Mulawarman University, Samarinda. Sources of research data in this study is primary data obtained through questionnaires with a Google form. The sample in this research is students of Faculty of Medicine, Mulawarman University, which amounted to 177 students consisting of Study Programs of Medicine, Dentistry, and D-3 Nursing. Bivariate analysis was done using Chi – Square test. The results of the research showed that many students of the Faculty of Medicine, Mulawarman University, Samarinda experienced symptoms of CVS (82.5%), the symptoms of CVS is experienced by many students (73,4%) who use a smartphone with duration of ? 4 hours / day (p = 0.000) and 59.9% viewing distance of < 29,2 cm (p = 0.001). It was concluded that there is a relationship between the duration and distance of smartphone’s usage with the symptoms of CVS in students of the Faculty of Medicine, Mulawarman University, Samarinda Key Words : Duration, Viewing Distance, Computer Vision Syndrome, Smartphone